To See what Jan Karoł Chodkiewicz Saw, or Some Profiles of the Hetman’s Votive Image - Račiūnaitė, Tojana (Senoji Lietuvos literatūra, 2024)
When studying historical visual monuments, we usually take up the position of an observer, but one can also study historical observers, historical people as consumers of visuality and the owners of an active gaze. In such a case, the focus of the study encompasses not only the monuments that represent an individual but also the individual’s gaze, the visual surroundings recorded in the written sources, the connection with specific art works or the phenomena of the history of art. Using the notion of gaze as an expression of power and protection, which was embedded in art history by the works of Hans Belting, David Freedberg, and others who applied visual anthropology methods, this article presents several aspects of Jan Karol Chodkiewicz’s ‘votive portrait’. A votive portrait is defined as a specific image of a person intended to convey an encoded connection between the portrayed and the saint that manifests through prayers, offerings, and vows. This connection can be presented visually, or it can exist only in written historical or literary sources. In this study, the notion of a ‘votive portrait’ conceptualises an attempt to connect fragmentary testimonies with the cultural phenomena characteristic of the early-seventeenth-century Grand Duchy of Lithuania, with those ‘collective formations’ in which a certain tendency, an inclination, or, in the words of Clifford Geertz, a ‘sensitivity’ can be felt. Analysis of diverse written sources – works of early literature such as Laurentius Boierus’ Carolomachia (1605) and Matthias Casimirus Sarbievius’s Sacra lithothesis (1621), Chodkiewicz’s private correspondence (mainly letters to his wife Zofia and his steward Kamieński), and several privately funded church visitation records – reveal new facts about Chodkiewicz’s relationship with the depictions of the saints. The study confirmed that figures of St Casimir, St Michael the Archangel, the Blessed Virgin Mary can be considered the most evident aspects of Chodkiewicz’s piety. It is notable that Chodkiewicz’s devotion to the aforementioned saints, which was recorded in Boierus’s poem and echoed in other sources, is closely linked to the specific depictions of saints and places of their cult. The outline of art perception, which is recorded in Chodkiewicz’s correspondence, correlates with the early seventeenth-century polemical discourse about the meaning and purpose of the depictions of saints and captures the collective ‘sensitivity’ of the epoch to certain forms and types of visuality. In Chodkiewicz’s letters, references to images indicate their religious and commemorative (memorialising) functions; the notion of the relationship with an image resonates with the pragmatic theory of art embedded in the seventeenth-century scripture, where images (whether secular portraits or religious paintings) are intended for remembrance and infusion of love and can themselves become objects of passion and love. The context of seventeenth-century ecclesiastical art, which also includes the phenomenon of the import of a Muscovite icon, allows explaining previously uncommented or misinterpreted parts of Chodkiewicz’s letters: the research revealed that the word ‘Muscovite’ refers to an icon, i.e., an image of the Mother of God, and not to a living person as interpreted by previous authors. However, the literary and historical sources consulted suggest that some donations were accompanied by votive motifs, i.e., vows made and taken as well as certain circulation of sacrifices, prayers of trust and intercession. The Church of the Annunciation to the Blessed Virgin Mary in Kretinga can be regarded as such a votive donation of Chodkiewicz. Unlike others – Kražiai, for example – it materialised. Moreover, Chodkiewicz’s exceptional relationship with the Bernardine order is evidenced by the establishment of the family mausoleum in the crypt of the church in Kretinga, the consecration of his son to the Bernardine order, the donations to the Bernardines of Vilnius (for the organ and the high altar), the choice of a Bernardine as a confessor in Ostrog, and the like. On the other hand, as early as 2 September 1603, in Cracow, the Bernardines handed Chodkiewicz a letter of spiritual privileges signed by General Minister F Iosephus Piscullius Melfiensis. The sponsorship of the Jesuit church in Kražiai was promised but never fully realised, just like in Ostrog. In this remote place, across the entire territory of the Grand Duchy of Lithuania, in these places, at opposite ends of the vast territory of the Grand Duchy of Lithuania, Chodkiewicz took his last vows in the face of the war with Turkey in 1621.